Rapid and sustained antidepressant effects of tubastatin A in a mouse model of depression - Masahide Fukada; Yoshiharu Kawaguchi; Atsuo Nakayama (Scientific Reports)
Abstract Depression is a prevalent mental disorder and a leading risk factor for suicide. Conventional antidepressants, which target the monoaminergic system, often have delayed therapeutic effects and limited efficacy. Therefore, the development of faster-acting and more effective treatments is critical. We previously showed that a single dose of an histone deacetylase 6 (HDAC6) inhibitor reduced behavioral despair in wild-type mice, suggesting the therapeutic potential of HDAC6 inhibition. In this study, we evaluated the effects of tubastatin A (TubA), a selective HDAC6 inhibitor, in a chronic corticosterone-induced mouse model of depression. Behavioral assessments using the female-encounter test and forced swim test revealed that a single dose of TubA reversed anhedonia within 24 h, with effects persisting for at least one week. TubA also enhanced exploratory behavior and reduced behavioral despair. Mechanistically, TubA activated extracellular signal-regulated kinase signaling in the brains of chronic corticosterone-treated mice 24 h post-injection. These findings suggest that TubA exhibits rapid and sustained antidepressant effects, offering promise as a novel therapeutic strategy for depression.